“PARABASIS” IN THE ANATOMY LESSON BY DANILO KIŠ (Heritage, 2020)
The research focus of this paper is the chapter “Parabasis” of the polemical book The Anatomy Lesson by Danilo Kiš. The author aims to draw a parallel with the genealogical characteristics of the parabasis in ancient comedy to explain its function in The Anatomy Lesson and to examine the veracity of Kiš’s self-interpretation, and thus the justification of his creative self-consciousness.
Keywords: Danilo Kiš, polemic, Anatomy Lesson, parabasis, irony, autopoetics, Jewishness, Borges, documentariness, intertextuality.